2019
DOI: 10.1016/j.ecolind.2019.105514
|View full text |Cite
|
Sign up to set email alerts
|

Developing practical techniques for quantitative assessment of ecosystem services on farmland

Abstract: The application of the concept of ecosystem services in the context of environmental management of agricultural landscapes is a relatively new and developing topic. There is increasing demand for the delivery of ecosystem services, especially with respect to ensuring that outcomes from policy interventions are realised. Consequently, there is a need for knowledge, tools and techniques to aid the identification of appropriate options for the given circumstances. This paper presents the outputs from a study that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
(64 reference statements)
0
4
0
2
Order By: Relevance
“…This revealed that some highly productive agricultural regions of Europe, such as Brittany in France and the Po Valley in Italy, potentially have good levels of biological control provided by flying natural enemies, while in other highly productive regions, such as the Central Loire Valley in France and the East-Midlands in the UK, the biological control potential was estimated to be low. Finally, the quantitative data generated in QuESSA was incorporated into an existing prototype software package (the Ecological Focus Areas Calculator) [45]. This software allows the user to assess the performance of land use and landscape features on a range of ecosystem services including biological control [46].…”
Section: Approach Based Upon Measurement Of Predation or Parasitismmentioning
confidence: 99%
“…This revealed that some highly productive agricultural regions of Europe, such as Brittany in France and the Po Valley in Italy, potentially have good levels of biological control provided by flying natural enemies, while in other highly productive regions, such as the Central Loire Valley in France and the East-Midlands in the UK, the biological control potential was estimated to be low. Finally, the quantitative data generated in QuESSA was incorporated into an existing prototype software package (the Ecological Focus Areas Calculator) [45]. This software allows the user to assess the performance of land use and landscape features on a range of ecosystem services including biological control [46].…”
Section: Approach Based Upon Measurement Of Predation or Parasitismmentioning
confidence: 99%
“…Andersen 等 [22] 、 Cao 等 [23] 王成等 [13] 、 范业婷等 [24] 、 赵华甫等 [25] Jiang 等 [17] 、 Liu 等 [18] 、 邹利林等 [21] 、 Zhang 等 [26] 、 张英男等 [27] 、 Lv 等 [28] 半自然生态系统调节基本生态过程和生命支持系 统的能力 [29][30][31] , 例如生物多样性保护、 气候调节和水 源涵养等; 而文化功能是指耕地作为景观所提供的 审美功能、 文化休闲及游憩等功能 [32] 。需要指出的 是, 耕地多功能并不是单独存在, 非此即彼, 而是相 互联系和相互作用的综合体; 生产功能和生态功能 是耕地资源系统最为核心和直接的两个功能, 而生 活功能和文化功能是人类社会系统在利用耕地资 源过程中衍生出的间接功能 [33] 。 2.2 耕地多功能供给的内涵及表征 耕地多功能供给是自然过程和社会条件的耦 合链接, 是耕地系统与人口系统、 经济系统、 社会系 统及资源系统相互作用的结果 [17] 。部分学者对耕地 多功能供给的识别、 表征及评估开展了较为丰富的 研究, 大致可分为以下 5 种方式 (表 2) : ①基于专家 经验排序的功能量化方法。通过建立土地利用类 型与生态系统服务间的对应关系, 采用供给矩阵等 定性方法分析耕地多功能的供给特征 [12,34] 。②基于 直接或者加权指标作为近似值的功能量化方法。 主要采用土地利用、 社会经济、 农业生产及夜间灯 光等数据, 经过标准化处理及加权等方式来构建综 合评价指标体系及无量纲的功能值或指数, 评估耕 地多功能供给的时空变化 [27,28,[35][36][37][38][39][40] 。③借鉴资源环境 经济学的价值核算方法, 通过将耕地提供产品和服 务的物质量转换为货币来核算 [41][42][43][44] 。④基于能值的 功能量化方法, 将耕地提供的产品和服务转换为太 阳能等来核算 [45][46][47] 。⑤基于生物物理模型的功能量 化方法, 主要从物质量的角度, 对耕地功能发挥过 程中物质循环进行定量评估 [48,49] 为间接性指标, 如空气质量和水资源量等 [38] 。耕地 具有多种功能是客观存在的, 但是人们对耕地功能 的认识和需求随着社会经济发展却是不断深入和 演变 [15] , 例如, 在农业社会, 因物质生活资料极度短 缺, 耕地的生产功能受到极大重视; 而在当前进入 工业化后期, 由于生态环境的恶化, 人类对于耕地 的生态和景观文化功能需求增强 [50] 。为了评估一定 时期人类对耕地多功能的需求, 需要通过社会经济 图 1 耕地多功能分类概念框架…”
Section: 代表性文献unclassified
“…The accounting index of GEP was divided into three major services and six smaller classes. We chose the ecological services described above because previous studies have shown their importance to cropland ecosystems, and we had available data and methods to evaluate their value according to the Technical Guideline on Gross Ecosystem Product (Yuan et al, 2011;Li et al, 2016;Tzilivakis et al, 2019;Cai et al, 2020). Material services, regulating services, and cultural services are accounted for in Eq.…”
Section: The Technical Framework Of China's Cropland Ecosystem Assess...mentioning
confidence: 99%